2017
DOI: 10.3390/toxins9090287
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal bZIP Transcription Factor AtfB Controls Virulence-Associated Processes in Aspergillus parasiticus

Abstract: Fungal basic leucine zipper (bZIP) transcription factors mediate responses to oxidative stress. The ability to regulate stress response pathways in Aspergillus spp. was postulated to be an important virulence-associated cellular process, because it helps establish infection in humans, plants, and animals. Previous studies have demonstrated that the fungal transcription factor AtfB encodes a protein that is associated with resistance to oxidative stress in asexual conidiospores, and AtfB binds to the promoters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
1
21
0
3
Order By: Relevance
“…The 15 nutrient competition-related genes include nine YAP, four ATF2, one Zip1 and one u1 genes, while the 15 pathogen interaction-related genes include eight YAP, four ATF2, one Zip1, one u1 and one BRLZ genes. These results suggest that YAP and ATF2 proteins in T. asperellum may be involved in various stress responses, similar to other homologs 9,15,[34][35][36][37] . One BRLZ gene was significantly downregulated in N-Hungry media (interaction with pathogens), and a homolog of this protein is reportedly involved in fungal development and differentiation 38 .…”
Section: Discussionsupporting
confidence: 54%
“…The 15 nutrient competition-related genes include nine YAP, four ATF2, one Zip1 and one u1 genes, while the 15 pathogen interaction-related genes include eight YAP, four ATF2, one Zip1, one u1 and one BRLZ genes. These results suggest that YAP and ATF2 proteins in T. asperellum may be involved in various stress responses, similar to other homologs 9,15,[34][35][36][37] . One BRLZ gene was significantly downregulated in N-Hungry media (interaction with pathogens), and a homolog of this protein is reportedly involved in fungal development and differentiation 38 .…”
Section: Discussionsupporting
confidence: 54%
“…Numerous studies have reported that catalase is a vital virulence component in the pathogenic fungi, such as A. parasiticus (Wee et al, 2017), C. albicans (Uehara et al, 2006) and A. fumigatus (Paris et al, 2003;Shibuya et al, 2006;Shin and Yu, 2013). To address the effect of CTA1 on A. flavus pathogenicity, we detected seeds infection in the ΔCTA1 mutant, and the results showed that the deletion of cta1 leads to exuberant colonization and increased number of conidia in both peanut and maize seeds ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two transcription regulators MeaB and RtfA, was previously identified as negative regulators ( Amaike et al, 2013 ; Lohmar et al, 2016 ), and their expression levels were significantly downregulated in YES when compared with in YEP, but seems not to be regulated by AfRafA or AfStuA in this study ( Figures 6A,B ). Unexpectedly, the bZIP TF AtfB, positively regulating AF biosynthesis ( Wee et al, 2017 ), its transcription level was downregulated by twofold in YES vs. in YEP, whereas upregulated by threefold in Δ AfStuA mutant in compassion to WT ( Figure 6C ), implying that AfStuA regulates AF in an AtfB-independent way. G protein-coupled receptor gene gprP was up-regulated in all strains used in YES compared with WT cultured in YEP ( Figure 6D ), and its encoding protein negatively control the AF biosynthesis ( Affeldt et al, 2014 ).…”
Section: Resultsmentioning
confidence: 96%